Transformed through the CARTA experience: changes reported by CARTA fellows about their PhD journey - Anne Ruhweza Katahoire; Jill Allison; Marta Vicente-Crespo; Sharon Fonn (Taylor & Francis Group, 2023)
Transformative learning occurs when a person, group, or larger social unit encounters ideas that are at odds with their prevailing perspective. This discrepant perspective can lead to an examination of previously held beliefs, values, and assumptions. The Consortium for Advanced Research Training in Africa (CARTA) has since 2011 been training and supporting faculty from different African universities, to become more reflective and productive researchers, research leaders, educators, and change agents who will drive institutional changes in their institutions. As part of a mid-term evaluation of CARTA, an open-ended question was posed to the CARTA fellows asking them to describe any changes they had experienced in their professional lives as a result of the CARTA Programme. The 135 responses were inductively coded and analysed using qualitative thematic analysis. These themes were subsequently mapped onto Hoggan's typology of transformative learning outcomes. CARTA fellows reported shifts in their sense of self; worldviews; beliefs about the definition of knowledge, how it is constructed and evaluated; and changes in behaviour/practices and capacities. This paper argues that the changes described by the CARTA fellows reflect transformative learning that is embedded in CARTA's Theory of Change. The reported transformation was enabled by a curriculum intentionally designed to facilitate critical reflection, further exploration, and questioning, both formally and informally during the fellows' PhD journey with the support of CARTA facilitators. Documenting and disseminating these lessons provide a guide for future practice, and educators wishing to revitalise their PhD training may find it useful to review the CARTA PhD curriculum.